2021
DOI: 10.3989/scimar.05128.008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the female attendance pattern and pup growth rate in the South American sea lion (Carnivora)

Abstract: Changes in the duration and frequency of foraging trips by female otariids may result in changes in the duration and frequency of lactation bouts and hence influence pup growth rate, unless females modify milk energy density and/or the total amount of milk delivered depending on the trip duration. To test this hypothesis on South American sea lions, we measured two attendance pattern components (foraging trip and haul-out duration) and three diving behaviour components of nursing females (dive time, bottom tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Hastings et al (2021) found that in certain rookeries in both the eastern and western DPSs, earlier weaned yearlings had a lower probability of survival and that heavier pups were more likely to wean by one year of age. Applying these concepts to our findings, it is possible that the larger pups in the western portion of the range incur a larger burden on lactating females (as was found in South American sea lions, Otaria flavescens, who foraged longer for heavier pups; Drago et al, 2021) and may habitually be weaned sooner and therefore ultimately experience lower survival rates despite their larger size. It could also be that resource limitations in the far western regions lead females to spend more time foraging during the summer and therefore less time nursing pups.…”
Section: Age-and Sex-specific Comparisonsmentioning
confidence: 54%
“…Hastings et al (2021) found that in certain rookeries in both the eastern and western DPSs, earlier weaned yearlings had a lower probability of survival and that heavier pups were more likely to wean by one year of age. Applying these concepts to our findings, it is possible that the larger pups in the western portion of the range incur a larger burden on lactating females (as was found in South American sea lions, Otaria flavescens, who foraged longer for heavier pups; Drago et al, 2021) and may habitually be weaned sooner and therefore ultimately experience lower survival rates despite their larger size. It could also be that resource limitations in the far western regions lead females to spend more time foraging during the summer and therefore less time nursing pups.…”
Section: Age-and Sex-specific Comparisonsmentioning
confidence: 54%
“…In some species, peak lactation may require 3‐6 months depending on the typical duration of lactation ( Costa and Valenzuela-Toro, 2021 ). Interestingly, in otariids, no relationship has been found between percentage milk fat female mass, or time on shore before milk collection; however, longer foraging trip duration results in greater milk fat composition ( Arnould and Boyd, 1995 ; Drago et al, 2021 ). The increased energy density of milk compensates for the additional energy costs pups incur due to extended fasting duration such that neither pup growth rate or rate of milk energy delivery is impacted by the time females are away from the pup ( Arnould and Boyd, 1995 ; Drago et al, 2021 ).…”
Section: Pinniped Milkmentioning
confidence: 99%
“…In sexually dimorphic otariids, differential growth patterns are observed between male and female pups related to maternal provisioning (suckling bout duration, milk energy density, duration of lactation) and food availability (environment quality). In general, females receive greater fat milk that is not limited by maternal resources or food availability, while males receive reduced fat milk and provisioning may be limited when the cow has reduced energy reserves ( Georges and Guinet, 2000 ; Drago et al, 2021 ). Research in other pinniped species have found both no differences in provisioning between sexes and some difference that are hypothesized to relate to pup mass, not sex ( Salogni et al, 2018 ; McHuron et al, 2023).…”
Section: Pup Mass and Growthmentioning
confidence: 99%
“…Female SASLs nurse their pups for 8-10 months (Campagna & Le Boeuf 1988). Male pups grow more slowly and demand extra energy investment from their mothers (Drago et al 2021).…”
mentioning
confidence: 99%